Dampak Toxic Relationship terhadap Self-Esteem Korban Kekerasan dalam Pacaran pada Mahasiswa - Azaria, Ihda A`yunil; Aliza, Novia Fetri (POROS ONIM: Jurnal Sosial Keagamaan, 2024)
This study examines the impact of toxic relationships on the self-esteem of students who are victims of dating violence. This study is important to conduct because our society is mostly only concerned with violence that is within the scope of legitimate bonds such as domestic violence but is still unfamiliar with violence against in dating relationships. Students were chosen by researchers to be the objects of this study because students are considered educated people, but in fact not many students know about the forms of violence in dating, even unknowingly becoming victims of such violence. Therefore, violence in dating relationships is very important to study as a form of concern and to provide information to young couples (students) so that they do not get caught in toxic relationships. With a qualitative-descriptive approach based on case studies, data were obtained through semi-structured interviews, unstructured observations, and documentation. Subjects experienced toxic relationships in the form of emotional violence (verbal abuse, dominance, possessiveness) and psychological manipulation (gaslighting, guilt-tripping, love-bombing). The impacts include loss of self-control, low self-acceptance, self-harming behavior, and doubt in decision making. These findings indicate the importance of psychological interventions to restore the self-esteem of victims of dating violence and to increase awareness of the dangers of toxic relationships among students.